(untitled) (Research, Society and Development, 2020)
The institution of the Unified Health System (SUS), in 1988, demanded a new model of health promotion, which requires a different profile in the education of health professionals through the commitment to SUS principles and guidelines and to care beyond of the pathological process. SUS becomes a guiding principle in the education of health professionals, which requires higher education institutions to return to health training in order to be committed to the socio-health reality. This study aims to evaluate the student experience in the extramural experience provided by the discipline Health and Citizenship (SACI). This is a qualitative, exploratory-descriptive study based on focus groups submitted to the content analysis technique with the aid of the IRAMUTEQ software. The students’ speeches emerged from sensitive experiences that recognized the relevance of comprehensive care and teamwork for a broader assistance to the population. It is concluded that through transformations in the curricular structures guided by the principles of the Unified Health System, they allow experiences such as SACI to integrate the training of health professionals and contribute to a change in health practice.